Replacement of fishmeal by vermimeal in the diets for sex reversed tilapia, Oreochromis massambicus (Peters) fry reared in a closed recirculating system. - Papalid, Leonila V. (College of Fisheries, University of the Philippines in the Visayas, 2008)
A nine-week feeding trial was conducted to evaluate the use of vermimeal (VM) as a replacement for Peruvian fishmeal (PFM) protein in the diets for sex reversed tilapia. Oreochromismossambicus (Peters) fry grown to fingerling stage. Five isonitrogenous (40% CP), isolipidc (7% CF) and isocaloric (3.51 kcal GEg1) test diets wee formulated in which VM replaced 0 (DI, control), 25 (D2), 50 (D3), 75 (D4), and 100% (D5) of the animal protein supplied by PFM. The study was conducted in 200 liters conical fiberglass tanks with closed type water recirculating system. Twenty-one days old sex reversed tilapia fry (0.1512g + 0.004) were randomly stocked at 50 pieces/tank and fed diets at weekly adjusted rations four times daily at 0900, 1200, 1400,1600h, six days a week. Physico-chemical parameters of the water were within the desirable range for tilapia fry. Growth performance (wt. gain, % wt. gain, and specific growth rate) of fish fed diets containing VM at 25 and 50% level of replacement for PFM protein (diets 2 and 3) were highly comparable with the control group (DI). A highly significant decrease in growth was noted when fishmeal protein substitution was increased to 75 and 100% vermimeal. Feed conversion ratio (FCR), feed conversion efficiency (FCE) and percent protein retention exhibited the same trend. On the basis of protein efficiency ratio (PER), fish fed D1 and D2 were statistically comparable. There was also no statistical difference was also observed between D2 and d3. Fish fed the maximum dietary protein from VM significantly displayed the highest lipid retention of 129.82% followed by, in descending order, D4, D3, D2, and D1 with lipid retention values of 93, 70, 80.87, 64.28, and 24.39% respectively. Higher condition factor (K) were also found in fish fed D5 and was significantly higher than those fed fishmeal as the sole source of animal protein (DI). No significant differences in condition factor were observed among fish fed diets with vermimeal inclusion (D2, D3, D4 and D5). Survival rates were relatively high and were not significantly affected by the VM substitution in the diet. Body composition analysis showed that carcass protein is no significantly affected by dietary VM. However, a significant increase in carcass lipid was found in diets containing vermimeal. These results showed that 50% of Peruvian fishmeal protein could be replaced by vermimeal protein in the diets sex reversed tilapia, Oreochromismossambicus fry without significantly affecting feed utilization efficiencies and growth parameters. Further studies on the supplementation of sulfur containing amino acids, use of feed attractants and use of vermimeal for fattening tilapia before harvest are suggested.